Mental Rotation as an Indicator of Motor Representation in Patients with Mild Cognitive Impairment - Bourrelier, Julien; Kubicki, Alexandre; Rouaud, Olivier; Crognier, Lionel; Mourey, France (Frontiers in Aging Neuroscience, 2015)
This internal representation of movement of part(s) of the body is involved during Implicit Motor Imagery tasks (IMI); the same representations are employed in the laterality judgment task. Few studies have looked at the consequences of aging, Alzheimer’s disease (AD) and mild cognitive impairment (MCI) on the processes of motor preparation but none showed evidence of an alteration of action representation in patient with amnestic MCI. In the present study, the IMI task was used to assess the action representation abilities in MCI patients and healthy counterparts. A total of 24 elderly participants aged between 65 and 90 years old (12 women, 73.4 ± 6 years, mean ± S.D.) were recruited: 12 patients with MCI (MCI group) and 12 healthy aged adults (HAA group). The results showed that MCI patients have significantly a greater response time (RT) than HAA subjects only in IMI task and more precisely when performing their mental rotation at the challenging conditions. Furthermore, the IMI task related to the non-dominant hand induced a significant increase of RT only in MCI subjects. At the light of these results, we assume that MCI patients are able to engage themselves in implicit motor imagery processes, still showing a compelling impairment of this mental ability across its complexity.